Effects of normalizing heat treatment on the mechanical and magnetic properties of the puddled iron. (April 2023) - Benini, L.; Pardal, J.M.; Tavares, S.S.M.; Renni, Y.S.; Oliveira, I.G.; Noris, L.F.; Correia, J.A.F.O.
Highlights: Mechanical and magnetic properties characterization of the century-old structure's current state. Identification of the unknown manufacturing process from an ancient Bridge's component. Ferritic microstructure of heterogeneous size grains containing numerous coarse non-metallic inclusions that lead to low toughness values at room temperature. Barkhausen Noise results reveal the distinction of an easy magnetization axis aligned with the forming process direction. Potential of application of the non-destructive technique for characterization of structural components in loco. Abstract: In the mid-19th century, with the advent of the industrial revolution, the puddled iron was the main metallic material produced on a large scale to meet the existing demand in the manufacture of large riveted structural components, such as railway bridges, thus representing a technological advance in this period. Due to the incipient metallurgical knowledge of the time and the fact that corrective maintenance may have been carried out during the lifetime of the components, such as localized heating and/or welding that might not be suitable for this type of material, the study of this class of material becomes important since many of the structures made with it are still in operation. Furthermore, its heterogeneous characteristics, inherent to its manufacturing process, make it difficult to characterize it and there is little information about the status of the microstructure and mechanical properties of these structures, making the application of non-destructive characterization techniques appealing in this scenario. Thus, the present work is based on the characterization of the effects of the microstructure on the mechanical and magnetic properties of samples of puddled iron taken from a component in service for approximately 150 years and compared when subjected to a normalizing heat treatment. The results denote a ferritic microstructure of heterogeneous grain size containing numerous coarse nonmetallic inclusions that result in low tenacity values at room temperature both in specimens obtained from samples as received and normalized, although in the thermally treated condition a higher value of ferritic grain size, on average, was obtained which promoted a slight decrease in the hardness values. These phenomena were characterized by magnetic measurements of magnetic Barkhausen Noise (MBN) allowing the distinction of an easy magnetization axis aligned with the conformation direction of the evaluated components. Therefore, a great potential is exhibited in the non-destructive characterization of this class of material, although several standards are required to obtain a calibration curve with the evaluated properties.